Art and the Heideggerian Repression: Ranciére, Nancy, and a Communism of the Image. Issue 1 (3rd September 2013) - Eng, Michael
Abstract : This essay conducts a reading of Jean-Luc Nancy's and Jacques Rancière's respective theorizations of the image. Using Nancy's notion of literary communism, I first show how he and Rancière conceive the image as a site of community's open writing and contestation. My reading then demonstrates how this "communism of the image" exposes Rancière's repetition of an ontological gesture that he has attempted to dismiss as Heideggerian.